Stress tensor changes related to fluid injection at The Geysers geothermal field, California. Issue 11 (7th June 2013) - Martínez‐Garzón, Patricia; Bohnhoff, Marco; Kwiatek, Grzegorz; Dresen, Georg
Abstract: [1] Studying variations of the stress field in reservoirs caused by massive fluid injection is important toward an improved understanding of geomechanical processes involved. We report on spatio‐temporal variations of the local stress tensor orientation at The Geysers geothermal field, California. We apply two stress inversion methods with detailed uncertainty assessments using a selection of events recorded between 2007 and 2012. Our results clearly indicate variations in the orientation of the principal stress axes for the reservoir as a whole showing a normal faulting regime at the reservoir depth between 2 and 3.7 km bounded by a strike‐slip regime above and below. Analyzing the temporal evolution of the stress tensor orientation for a prominent seismicity cluster we observe a clear correlation of changes in orientation for σ1–3 with the highest injection rates. These results suggest that temporal changes in the stress tensor orientation could contribute to characterize reservoirs during stimulation. Key Points: Fluid injection causes local temporal variations of the stress field orientation Long‐term fluid extraction results in changes of the stress regime with depth Stress inversion applied to microseismicity improves reservoir characterization